Clinical efficacy of the rotation of phototherapy methods (PUVA therapy and mid-wavelength ultraviolet therapy (311 nm)) in patients with moderate to severe forms of psoriasis - M. B. Zhilova; V. V. Chikin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To assess the therapeutic efficacy of the rotation of mid-wavelength ultraviolet therapy (311 nm) and PUVA therapy in patients with moderate to severe forms of psoriasis, and to assess the efficacy of mid-wavelength ultraviolet therapy (311 nm) in a multiple-course therapy. Materials and methods. The study involved 66 patients with moderate to severe forms of psoriasis who received multiple courses of treatment by methods of the PUVA therapy and narrowband mid-wavelength phototherapy (311 nm). The patients were divided into three groups: Group 1 (n = 20) - patients who received treatment in the form of mid-wavelength ultraviolet therapy (311 nm) after multiple courses of PUVA therapy; Group 2 (n = 26) - patients who received only multiple courses of PUVA therapy; Group 3 (n = 20) - patients who received only multiple courses of mid-wavelength ultraviolet therapy (311 nm). Results. The authors determined high efficacy (82.8%) of mid-wavelength ultraviolet therapy (311 nm) in patients with moderate to severe forms of psoriasis vulgaris who had previously received multiple courses of PUVA therapy. After multiple courses of long-term treatment by mid-wavelength ultraviolet therapy (311 nm), patients with moderate to severe forms of psoriasis had high efficacy of such multiple courses of treatment (85.78%). Conclusion. Patients with moderate to severe forms of psoriasis who had previously received multiple courses of PUVA therapy can be switched to mid-wavelength ultraviolet therapy (311 nm) with the maintenance of high efficacy of such treatment. The authors observed the absence of any adaptation to the spectral range of mid-wavelength ultraviolet therapy (311 nm) in case of multiple courses of treatment.